ANALISIS KINERJA HELM PELINDUNG DIRI PADA PEKERJA INDUSTRI MENGGUNAKAN SENSOR LIGHT DEPENDENT RESISTOR UNTUK MINIMALISIR KECELAKAAN - Mhd Rizki Syahputra; Adisastra Pengalaman Tarigan (Jurnal Nasional Teknologi Komputer, 2025)
Industry is a sector that requires special attention regarding worker safety. To increase the level of safety, the use of Personal Protective Equipment (PPE) connected to sensors is an innovative smart solution. By utilizing Internet of Things technology, the PPE system can provide real-time information regarding worker conditions and the work environment. Worker helmets are equipped with LDR sensors, which function to provide warnings to workers who are not wearing helmets and send information to the field supervision center via the Telegram application These sensors confirm the presence of workers and provide information about their activities. The LDR sensors are connected to a central monitoring system that enables real-time monitoring and rapid response to workers who are not wearing PPE helmets. This solution not only provides maximum protection against the risk of accidents, but also increases efficiency in safety management in industry. With automatic notifications and connection to a central system, this solution is a proactive step towards a safer and more efficient work environment in the industrial sector.